Inherited meanings of architecture: deconstruction of Rem Koolhaas' micro-floor and micro-wall narratives - Unal Basturk, Tuerkan Ceylan; Gorgulu, S. Tulin; Kaymaz, Senem (TAYLOR & FRANCIS LTD, 2025)
Inspired by zero degree writing, this article questions inherited meanings carried through social practices in architecture. To do this, it overlaps Roland Barthes's narrative codes with narratives of elements of floor and wall from Rem Koolhaas's book entitled Elements of Architecture. The aim of the research carried out in the article is to reach an assessment regarding zero degree cycles of inherited meanings of architecture in the narratives of two mentioned elements in Koolhaas's book. Methodologically, adapting Barthes's 5 narrative codes to deconstruct the floor and wall narratives in the relevant book builds a bridge that enables to achieve inherited meanings of architecture revealed by social productivity. As a result of the methodology, 26 productive terms which can be interpreted as inherited meanings of architecture are revealed. Productive terms open up architectural meanings to interpretation by mediating their conveys through social production and by turning into a living inheritance. The use of Roland Barthes' narrative codes in the deconstruction of an architectural text leads the article to an assessment of zero degree cycle of social productivity and reveals that architectural meaning is carried through social participation.
Keywords: Zero degree writing; narrative codes; micro-narratives; productive terms; inherited meaning of architecture; Architecture; Construction & Building Technology